Surveys and explorations by the Italian Archaeological Mission in Yemen in 1983 -1989. Résumé of the past activity and new research project: archive and publication of the results - Michael Jung; Khalid Ali al-Ansi (Disegnare con, 2020)
Since 1983, the Italian Archaeological Mission in Yemen (MAIRY) has also included research on the archaeological, architectural and fine arts heritage of the Islamic period in its activities The focus of the Islamic mission was study of Yemeni traditional mosques in order to draw up a precise typology of these unique monuments.  In the course of several expeditions, the mission surveyed over 400 monuments. Carrying out photographic and graphic documentation and drawing up plans the team drafted a first preliminary typology of the religious architecture in 1984. Nevertheless, for various reasons, the conclusion of the work and its outcome were never published. After thirty years, the Islamic branch of the Italian archaeological mission has resumed the research. The Italian team, in collaboration with Yemenite experts, is about to arrange, classify and digitalize the huge amount of documents. This documentation will constitute a major contribution to research on and the safeguarding of religious architecture and the Yemeni cultural heritage. DOI: https://doi.org/10.20365/disegnarecon.25.2020.11